A simplified technique for fabricating complete dentures for patients with Parkinson's disease: a case report - Luciana de Rezende Pinto; Ezequiel Caruccio Ramos; Monira Samaan Kallás; Fernanda Faot (Brazilian Society of Geriatrics and Gerontology, 2023)
Background and Objective: Parkinson's disease is a neurological disorder that affects 1% of individuals aged 60 years and older. The associated symptoms can impose limitations on the available dental treatment options. Case description: This case report follows the CARE guidelines and presents an adapted and simplified technique to fabricate complete dentures for a 74-year-old male edentulous patient with Parkinson's disease. This modified technique enabled the fabrication of complete dentures in 4 clinical sessions of approximately 40 minutes. The first session involved manufacturing a preliminary impression with fast-setting alginate. The base plates and occlusal rims were then adjusted for artificial teeth arrangement during the second session. The final prosthesis was completed in the third session, which involved a teeth try-in and fabrication of a functional impression with low-melting thermoplastic material and polyether. Finally, denture installation was performed in the fourth session and follow-up consisted of 3 weekly sessions. Discussion: Considering that the treatment provided satisfactory aesthetics and function, mastication and socialization benefits, and improved the self-esteem and well-being of the older patient with Parkinson's disease, the authors suggest this adapted and simplified technique for fabricating complete dentures.